1982
DOI: 10.1126/science.7089566
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Calcium in Human Hypertension

Abstract: A pilot survey was made of the dietary calcium intake of normotensive and hypertensive individuals. Compared to 44 normotensive controls, 46 subjects with essential hypertension reported significantly less daily calcium ingestion (668 +/- 55 milligrams compared to 886 +/- 89 milligrams). The intake of other nutrients, including sodium and potassium, was very similar in the two groups. The hypertensives differed from the controls primarily in their consumption of nonfluid dairy products. The data suggest that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 300 publications
(62 citation statements)
references
References 31 publications
4
57
1
Order By: Relevance
“…[1][2][3][4][5] However, since intake of these cations from drinking water generally represents only a small proportion of total intake, the role of dietary intake in relation to cardiovascular disease has become the focus of more recent investigation. Epidemiological and clinical research of the association of dietary calcium intake and BP has been extensively reviewed in recent years [6][7][8][9][10][11] including obtaining pooled quantitative estimates of effect. 7,11 However, less is known of the possible role of dietary magnesium on BP.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] However, since intake of these cations from drinking water generally represents only a small proportion of total intake, the role of dietary intake in relation to cardiovascular disease has become the focus of more recent investigation. Epidemiological and clinical research of the association of dietary calcium intake and BP has been extensively reviewed in recent years [6][7][8][9][10][11] including obtaining pooled quantitative estimates of effect. 7,11 However, less is known of the possible role of dietary magnesium on BP.…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1980s, two publications by McCarron et al (83,84) showed that low-Ca 2þ diets were associated with hypertension and that dietary Ca 2þ consumption by US adults was inversely related to the possibility of developing hypertension. A meta-analysis of forty-two clinical trials demonstrated significant blood pressure reduction by increasing Ca 2þ intake either in non-pregnant populations as well as pregnancy-induced hypertension and preeclampsia (85) .…”
Section: Relationship Between Dietary Ca 21 and Lipid Metabolismmentioning
confidence: 99%
“…1,6 However, data on the effects of dietary calcium on blood pressure have been inconsistent. Both noninterventional studies [7][8][9] and randomized clinical trials 10 -15 have yielded conflicting results on the effects of calcium intake on blood pressure and weight loss (from null effects to protective effects).…”
mentioning
confidence: 99%